THE INDONESIAN CORAL REEF REHABILITATION AND MANAGEMENT PROGRAM: LESSONS LEARNED IN COMMUNITY-BASED REEF MANAGEMENT ` AT SENAYANG AND LINGGA ISLANDS, RIAU - Dirhamsyah . (JOURNAL OF COASTAL DEVELOPMENT, 2006)
The Coral Red Rehabilitation and Management Program (COREMAP) is a I5-year program of the Government of Indonesia. It has been working at several sites in Indonesia since /998 to achieve sustainable use of coral reefs through the delegation of management authority to local communities. The establishment of epective models for participatory and community-based management is the core of this program. The model for community-based management includes community participation. community capacity building, promotion of alternative income generation, establishment of coral red management plans, community marine sanctuaries and community red watcher programs. This paper describes the experiences and lessons learned in Phase I of the COREMAP Project in implementing community—based red management at Senavang and Lingga Islands, Riau Province. It is argued that the involvement ofthe community in the planning and implementation process of coral reef management will improve the management and conservation of coral req' ecosystems. It is hoped that the Indonesian experience will contribute to the comparative literature on coral req' management.